ҚАРАҚАЛПАҚСТАНДА ОБЛЕПИХА (HIPPOPHAE L.) ӨСИМЛИГИНИҢ ИНТРОДУКЦИЯСЫ, БИОЭКОЛОГИЯСЫ ҲӘМ ХОЖАЛЫҚ ӘҲМИЙЕТИ - Отенова, Ф.; Отенов, Т.; Гулдурсунбаева, А.; Гроховатский, А. (FAN va JAMIYAT, 2016)
The article deals with the history of Hippophae L. introduction in conditions of Karakalpakstan, its biomorphological and ecological peculiarities, its possibility for seed duplication, and public economic importance as well.